MANUSIA SEBAGAI INDIVIDU (Analisis terhadap Kewajiban dan Tanggung Jawab) - Zainuddin Hamkah (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Every individual is not automatically able to realize his desires, but humans are forbidden to forget God while in the effort to realize these desires in the form of service obligations and responsibilities. For this reason, humans are given the freedom to choose between good and bad things. God himself has given trust to humans so that people always choose the good. God has made "freedom" an "ethical foundation" for humans to do. However, it turns out that there are many people who are unable to maintain God's trust; Most humans often choose bad deeds. The failure of religious obligations and irresponsibility is a form of human error in choosing freedom, and at the same time betrays God's trust in humanity. The failure of humans to fulfill their obligations and responsibilities is caused by the shortsightedness and narrowness of the human mind, and because of the shortsightedness and narrowness of the mind, humans often lose moral balance. In a long time, shortsightedness and narrowness of the mind will make the "conscience" of humans frozen, as a result humans increasingly away from the nature of events